Instrução de pobres e negros em Feira de Santana: as escolas do professor primário Geminiano Alves da Costa (1890 a 1920) - Oliveira, Daiane Silva (2016)
The aim of this work is to approach the institution process of Feirense school in the late nineteenth century and early twentieth century, centralizing school practices the black professor Geminiano Alves da Costa and its primary classes for children and adults in the city of Feira Santana from 1890 to 1920. the research has bases in the propositions of the social History of Education, highlighting the so-called school subjects and their daily experiences intra and extra school, for an understanding of the web of relationships that guided the experiences of that subject as a social phenomenon to be appropriate. The purpose of the work that follows is a directed approach to ownership of the black professor Geminiano Alves da Costa as a cultural interlocutor, from a survey of data on its roundness in feirenses spaces from that, the data supported the research as suggested Ione Sousa (2008), in looking perspective to the subject in a more detailed, more distant from large institutions in order to view the tiny experiences of literacy, literacy, their meanings for the subjects involved, and leaves aside the concern with great educational ideas and educational systems. From the experience of this subject we seek to embed Feirense educational scene in the early republican period, milestone that determined our cut and highlight the professional identity of these subjects students of schools, intertwined with the Geminiano Costa teacher.